2020
DOI: 10.1038/s41598-020-61494-1
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated identification of serine racemase inhibitor from Centella asiatica

Abstract: Serine racemase (SR) converts the free form of L-serine into D-serine (DS) in the mammalian brain. The DS functions as a co-agonist of N-methyl D-aspartate (NMDA) receptor. The over-activation of NMDA receptor leads to many neurological disorders like stroke, amyotrophic lateral sclerosis, Alzheimer's disease and an effective inhibitor of SR could be a corrective method for the receptor over-activation. We report for the first time here a rapid way of purifying and identifying an inhibitor from medicinal plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…It would be interesting to determine whether such compounds utilize the Tyr 121 pocket. In 2020, it was reported that the natural product madecassoside is an inhibitor of SR 49 , although a supporting co-crystal structure has not yet been solved. While malonate and related acids (Supplementary Table 6 ) remain useful tool compounds, they are likely too polar to be developed as drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to determine whether such compounds utilize the Tyr 121 pocket. In 2020, it was reported that the natural product madecassoside is an inhibitor of SR 49 , although a supporting co-crystal structure has not yet been solved. While malonate and related acids (Supplementary Table 6 ) remain useful tool compounds, they are likely too polar to be developed as drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 paper published an inhibitor of mouse SR, 13 J, that could suppress neuronal overactivation in vivo 39 and produced better IC 50 values (140 µM) than malonate (770 µM). In 2020, a novel plant derivative SR inhibitor, madecassoside (IC 50 26 µM), was reported and described as a far better inhibitor than malonate (IC 50 449 µM) 49 . IC 50 values are known to be dependent on conditions under which they are measured.…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to determine whether such compounds utilize the Tyr 121 pocket. In 2020, it was reported that the natural product madecassoside is an inhibitor of SR 55 , although a supporting co-crystal structure has not yet been solved. While malonate and related acids (Supplementary Table 6) remain useful tool compounds, they are likely too polar to be developed as drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 paper published an inhibitor of mouse SR, 13J, that could suppress neuronal overactivation in vivo 38 and produced better IC 50 values (140 μM) than malonate (770 μM). In 2020, a novel plant derivative SR inhibitor, madecassoside (IC 50 26 μM), was reported and described as a far better inhibitor than malonate (IC 50 449 μM) 48 . IC 50 values are known to be dependent on conditions under which they are measured.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together the degradation of l -β-EHAsn by Dsd1p and its inhibitory effects on serine racemase, results suggest the involvement of l -β-EHAsn in metabolic regulation of pathways related d -ser. Unfortunately, it has not been shown that l -β-EHAsn inhibits human serine racemase, a more relevant model; if this inhibition is proven true, modified versions of l -β-EHAsn could serve as new start points for drug discovery programs targeting human serine racemase [ 7 ].…”
Section: Commentarymentioning
confidence: 99%